Development of scenario management and requirements tool (SMaRT): towards supporting scenario-based requirements engineering methodology - Nordin, Azlin; Ikhwan Omar, Amirul; Usamah Megat Mohamed Amin, Megat; Salleh, Norsaremah (International Journal of Engineering and Technology, 2018)
Scenario-based methodology has been applied in analyzing real world experience into representation in software environment. Nonetheless, capturing, documenting and managing scenarios are extremely labor-intensive. Hence, the generic aims of this project are to investigate, explore and analyze requirements management process towards supporting scenario-based requirements approach. Based on our analysis of the existing RE or Requirements Management (RM) tools, most of the tools had less focus or missing some significant RE features to facilitate scenario-based   methodology. We analyzed all the relevant features and developed a prototype i.e.  Scenario-based Requirements Tool (SMaRT) to demonstrate how scenario-based approach can be implemented to further supports scenario-based RE  methodology and  covers most of the RE process  i.e. elicitation,  analysis  and  negotiation, documentation, validation,   and  management. SMaRT improves the RE tool features i.e. project and requirements management, document generation and validation function to further supports scenario-based RE methodology and covers most of the RE process i.e. elicitation, analysis, negotiation, documentation, validation, and management.